Assessing Funding Mechanism Available for Mining Companies in Zimbabwe - Kaseke, Nyasha; Mapakame, Gift (Journal of Economics and Behavioral Studies, 2021)
The mining sector has been the cornerstone of economic growth in Zimbabwe hence funding becomes very crucial to resuscitate the economy. The study aimed to assess the funding mechanisms for the mining sector of Zimbabwe and the effect of these on the performance of the sector. A quantitative study was carried out in the mining sector. The research findings showed that respondents pointed out that the funding mechanisms used in the mining sector of Zimbabwe are project finance, finance by private equity, public bonds and loans from banks and other financial institutions. It was also revealed that over and above available mechanisms, investment in the mining sector is being influenced by Interest rate, Business economic empowerment policies, bank lending criteria and Technical information, simultaneously. Furthermore, the study established that the mining sector needs skilled and technical staff, Technical information, banks’ lending criteria and Capital markets to get funding from investors. It was derived that, investment in the mining sector will increase production, product quality and profitability which in turn lead to infrastructural development. In addition, it is envisaged that funding will result in mining exports increase at the same time that new technologies are being introduced and the GDP is rising. Owing to the focus being exclusively on the funding of the mining sector, the study also recommended further studies on other factors, besides funding, that are affecting the performance of the sector.